2016
DOI: 10.1080/08927014.2016.1197210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon nanotubes and titanium dioxide incorporated in PDMS on biofilm community composition and subsequent mussel plantigrade settlement

Abstract: This study investigated the effect of carbon nanotubes (CNTs) and titanium dioxide (TiO2) incorporated in PDMS on biofilm formation and plantigrade settlement of Mytilus coruscus. TiO2 increased bacterial density, and CNTs also increased bacterial density but reduced diatom density in biofilms after 28 days. Further analysis was conducted between bacterial communities on glass, PDMS, CNTs (0.5 wt%) and TiO2 (7.5 wt%). ANOSIM analysis revealed significant differences (R > 0.9) between seven, 14, 21 and 28 day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 65 publications
(84 reference statements)
1
22
0
Order By: Relevance
“…In addition, a long-term investigation revealed the influence of biocide coatings on taxonomic structure of marine biofilms (Muthukrishnan et al 2014). More specifically, results of the present study are consistent with findings in recent studies of marine biofilm communities colonizing antifouling coatings, where Proteobacteria and Bacteroidetes were most affected by biocide coatings (Yang et al 2016;Briand et al 2017). Therefore, the enrichment of particular microbes in each biofilm group (such as Cycloclasticus enriched in the DCOIT-treated biofilms) implies that the compounds are less effective for some microbial taxa than for others during biofilm assembly.…”
Section: Sphingomonadaceae Spsupporting
confidence: 92%
“…In addition, a long-term investigation revealed the influence of biocide coatings on taxonomic structure of marine biofilms (Muthukrishnan et al 2014). More specifically, results of the present study are consistent with findings in recent studies of marine biofilm communities colonizing antifouling coatings, where Proteobacteria and Bacteroidetes were most affected by biocide coatings (Yang et al 2016;Briand et al 2017). Therefore, the enrichment of particular microbes in each biofilm group (such as Cycloclasticus enriched in the DCOIT-treated biofilms) implies that the compounds are less effective for some microbial taxa than for others during biofilm assembly.…”
Section: Sphingomonadaceae Spsupporting
confidence: 92%
“…When a biofilm colonizes the surface of macro-algae (Miranda et al, 2013) or animals such as cnidarians (Golberg et al, 2013), it can contribute to their development and defense (Bernbom et al, 2011). Biofilms also favor the attachment and metamorphosis of bivalves and other organisms (Anderson and Epifanio, 2009;Ganesan et al, 2010;Tebben et al, 2011;Yang et al, 2016aYang et al, , b, 2017. In aquaculture, biofilms have not been well studied up to now (Li et al, 2014;Yang et al, 2013), except in bioreactors of recirculating aquaculture systems (RAS).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a host of publications reported that AF coatings could influence and regulate the development of early-colonized bacterial communities [ 33 , 34 , 35 , 36 ]. However, a few publications have focused on the modulating effects of different PDMS-based nanocomposites on colonized pioneer bacterial communities in natural biofilms [ 37 , 38 ]. In the current study, most PCs demonstrated differential modulating effects on the colonization of pioneer prokaryotic microbes.…”
Section: Resultsmentioning
confidence: 99%